Dizzy triathlete-evidence supporting vestibular etiology - Manninen, I.-K.; Jutila, T.; Hirvonen, T.; Mäkinen, L. K.; Blomgren, K.; Hyytiä, T.; Klockars, T. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Dizziness during or after the swimming leg is a common complaint among triathletes. We hypothesized that the dizziness is caused by asymmetrical cooling of the vestibular organ. This caloric response is characterized by involuntary eye movements called nystagmus. Altogether, 125 triathletes completed an electronic questionnaire. Fifteen triathletes who had frequently experienced dizziness during the swimming leg agreed to take part in a cold water swimming test. The test comprised two cold water swimming legs, first without earplugs and then with earplugs to prevent a potential caloric response. Eye movements and possible nystagmus were recorded immediately after the swimming legs. A majority (87%, 109/125) of athletes had experienced dizziness during triathlon races or training. Of these, almost all (97%, 106/109) experienced it during or after swimming. Dizziness affected the triathlon performance in half of the athletes with dizziness (50%, 51/102). Fifteen athletes participated in a cold water swimming test. During the first leg (without earplugs), 11/15 athletes (73%) experienced dizziness. Of these, six had nystagmus (55%), four had uncertain nystagmus (36%), and one did not have nystagmus (9%). Only one of these athletes experienced dizziness during the second leg with earplugs. The prevalence of dizziness among triathletes is notable. A large part of the dizziness is likely to be caused by caloric reaction of the vestibular organ. We recommend earplug usage for triathletes suffering from dizziness during the swimming leg.